Design, synthesis and in vitro biological studies of novel triazoles with potent and broad-spectrum antifungal activity - Junhe Bao; Yumeng Hao; Tingjunhong Ni; Ruina Wang; Jiacun Liu; Xiaochen Chi; Ting Wang; Shichong Yu; Yongsheng Jin; Lan Yan; Xiaomei Li; Dazhi Zhang; et al. (Taylor & Francis Group, 2023)
A series of novel triazole derivatives containing aryl-propanamide side chains was designed and synthesised. In vitro antifungal activity studies demonstrated that most of the compounds inhibited the growth of six human pathogenic fungi. In particular, parts of phenyl-propionamide-containing compounds had excellent, broad-spectrum antifungal activity against Candida albicans SC5314, Cryptococcus neoformans 22-21, Candida glabrata 537 and Candida parapsilosis 22-20 with MIC values in the range of ≤0.125 µg/mL-4.0 µg/mL. In addition, compounds A1, A2, A6, A12 and A15 showed inhibitory activities against fluconazole-resistant Candida albicans and Candida auris. Preliminary structure-activity relationships (SARs) are also summarised. Moreover, GC-MS analysis demonstrated that A1, A3, and A9 interfered with the C. albicans ergosterol biosynthesis pathway by inhibiting Cyp51. Molecular docking studies elucidated the binding modes of A3 and A9 with Cyp51. These compounds with low haemolytic activity and favourable ADME/T properties are promising for the development of novel antifungal agents.